Analisis Yuridis Kebijakan Reskilling Pekerja dalam Menghadapi Disrupsi Otomatisasi Lapangan Kerja - Samsul Samsul; Yudhia Ismail; Humiati Humiati (Interdisciplinary Explorations in Research Journal, 2026)
The development of automation, digitalization, and artificial intelligence has brought significant changes to the structure of the labor market and poses the risk of reduced job opportunities for workers unable to adapt to technological developments. This study aims to analyze worker reskilling policies as an instrument for improving human resource competency in the era of automation and to examine legal regulations and government policies related to reskilling in response to job disruption in Indonesia. The research method used is a normative juridical approach, using statutory, conceptual, and case-based approaches. The data used is secondary data obtained through literature review and analyzed descriptively and analytically. The results indicate that reskilling has a legal basis in the Manpower Law, specifically regarding workers' rights to receive training and employers' obligations to improve workforce competency. However, existing regulations are still general in nature, do not explicitly stipulate reskilling as a legally enforceable right, and are not supported by effective enforcement mechanisms. Furthermore, government policies still face various obstacles, including regulatory fragmentation, weak institutional coordination, and the lack of integration of reskilling programs with the social protection system. Therefore, more comprehensive legal reform is needed through the establishment of specific regulations, strengthening training obligations for companies, and integrating reskilling policies with labor protection systems to achieve adaptive and sustainable protection in the era of automation.